PSCA is a target of chimeric antigen receptor T cells in gastric cancer - Wu, Di (Biomark Res, 2020)
BACKGROUND: Gastric cancer is a deadly malignancy and is a prognostically unfavorable entity with restricted therapeutic strategies available. Prostate stem cell antigen (PSCA) is a glycosylphosphatidylinositol (GPI)-anchored cell surface protein widely expressed in bladder, prostate, and pancreatic cancers. Existing studies have thoroughly recognized the availability of utilizing anti-PSCA CAR-T cells in the treatment of metastatic prostate cancer and non-small-cell lung cancer. However, no previous study has investigated the feasibility of using anti-PSCA CAR-T cells to treat gastric cancer, irrespective of the proven expression of PSCA on the gastric cancer cell surface. METHODS: We determined the expression of PSCA in several primary tumor tissues and constructed third-generation anti-PSCA CAR-T cells. We then incubated anti-PSCA CAR-T cells and GFP-T cells with target tumor cell lines at E:T ratios of 2:1, 1:1, 1:2, and 1:4 to evaluate the therapeutic efficacy of anti-PSCA CAR-T cells in vitro. We also assayed canonical T cell activation markers after coculturing anti-PSCA CAR-T cells with target cell lines by flow cytometry. The detection of a functional cytokine profile was carried out via enzyme-linked immunosorbent assays. We then evaluated the antitumor activity of anti-PSCA CAR-T cells in vivo by establishing two different xenograft GC mouse models. RESULTS: Anti-PSCA CAR-T cells exhibited upregulated activation markers and increased cytokine production profiles related to T cell cytotoxicity in an antigen-dependent manner. Moreover, anti-PSCA CAR-T cells exhibited robust anti-tumor cytotoxicity in vitro. Importantly, we demonstrated that anti-PSCA CAR-T cells delivered by peritumoral injection successfully stunted tumor progression in vivo. However, intravenous administration of anti-PSCA CAR-T cells failed to reveal any therapeutic improvements. CONCLUSIONS: Our findings corroborated the feasibility of anti-PSCA CAR-T cells and their efficacy against gastric cancer, implicating the potential of applying anti-PSCA CAR-T cells to treat GC patients in the clinic.